EFEK LAMA PENGERINGAN TERHADAP KADAR AIR GABAH DAN MUTU BERAS KETAN: Effect of Drying Time on Grain Moisture Content and Quality of Glutinous Rice - Arfiati Ulfa Utami, Rosiana Ulfa (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2022)
Glutinous rice is one of many varieties of rice grown in Indonesia. Glutinous rice differs from other varieties due to the higher content of amylopectin. One stages of rice processing that determines the quality characteristics of the rice is drying process. This process can be carried out directly under the sun or under the shade on the drying floor. Otherwise drying process also can be carried out in silo’s by utilizing wind gust to reduce the moisture content or the grain. In this study, the grain was dried on a drying floor using a tarp as a base for about 3, 4, 5, 6 and 7 days. The results showed that the grain which was dried for 3 to 4 days had a moisture content of 14%, the longer the grain dried, the water content of the grain will increase about 1-2%. The quality of the grain treated with the variation in drying time, showed that the longer drying time, the lower of whole rice produced and the more broken rice produced. Drying process in 3-4 days shows the percentage of broken rice and very small broken rice is about 21-22% and 1.6 until 1%. While drying at 5-7 days show the percentage of broken rice and very small broken rice is 24-27% and 1.3 until 7.1.